(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This study examines the concept of grammatical transformation as a fundamental aspect of English syntax, focusing on how sentence structures can change without altering their core meaning. Drawing on the principles of transformational-generative grammar, the research explores various types of transformations, including voice transformation (active–passive), sentence type transformation (declarative, interrogative, imperative), and negation. A qualitative descriptive approach is employed, using data collected from standard grammar textbooks, academic sources, and linguistic references.